A chitosan-sodium alginate-diatomite composite adsorbent, a preparation method and application thereof

CN119455906BActive Publication Date: 2026-10-09GUANGXI UNIV FOR NATITIES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411789765.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2026-10-09
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

本发明的创新方法有效解决了单一海藻酸钠水凝胶机械强度不足的问题,并显著增强了水凝胶微珠吸附剂的重复使用稳定性

Benefits of technology

[0037](1) In terms of preparation process, this invention ingeniously employs an innovative composite method. By carefully dripping a sodium alginate solution containing calcined diatomaceous earth into a carefully proportioned mixed solution of chitosan and CaCl2, sodium alginate-chitosan composite hydrogel microspheres are prepared, resulting in a composite adsorbent with a methylene blue removal rate of over 95%. This unique process not only cleverly combines the advantages of chitosan, sodium alginate, and diatomaceous earth, but also significantly improves the problem of insufficient mechanical strength in traditional single sodium alginate hydrogels. By introducing calcined diatomaceous earth, not only is the adsorption performance of the hydrogel microspheres enhanced, but its overall structural stability is also improved. Simultaneously, it provides diffusion channels for dye molecules within the microspheres, enabling the prepared chitosan-sodium alginate-diatomaceous earth composite adsorbent to exhibit higher durability and reliability in various complex environments. This innovation not only lays a solid foundation for the recyclability of hydrogel microsphere adsorbents but also greatly expands their scope and possibilities in practical applications, marking a significant technological breakthrough in the field of adsorption materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455906B_ABST
    Figure CN119455906B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a chitosan-sodium alginate-diatomic composite adsorbent, and comprises the following steps: (1) calcining and pretreating diatomic; (2) dissolving sodium alginate powder in water; (3) adding the calcined diatomic into the sodium alginate solution to prepare a mixed solution a; (4) dissolving CaCl2 in an acetic acid solution; (5) adding chitosan powder into the CaCl2 solution and stirring uniformly to prepare a mixed solution b; (6) dropping the mixed solution a into the mixed solution b to crosslink, and preparing SA / DM / CS composite gel balls; and (7) washing the gel balls with water for several times, repeatedly freezing and thawing for several times, and drying to prepare the composite adsorbent. The sodium alginate solution containing the calcined diatomic is dropped into the mixed solution of chitosan and CaCl2 to prepare the composite adsorbent, the problem of low mechanical strength of single sodium alginate hydrogel is solved, and the recycling stability of the hydrogel microbead adsorbent is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of adsorbent preparation technology, specifically relating to a chitosan-sodium alginate-diatomite composite adsorbent, its preparation method, and its application. Technical Background

[0002] As a major producer and consumer of textiles and dyes, my country accounts for 83% of the world's annual dye consumption. [1] The textile printing and dyeing industry consumes a large amount of water and generates a large amount of wastewater at every stage of the printing and dyeing process. Every year, 11% of industrial wastewater comes from wastewater generated from textile products. [2] Dyes have good solubility in water. Dye wastewater has a complex composition and is characterized by high color intensity, high chemical oxygen demand, difficulty in degradation, high toxicity, and difficulty in treatment. Therefore, dye wastewater, which is difficult to treat and highly hazardous, is one of the major industrial wastewaters in my country at present. [3-4] Currently, the main methods for treating dye wastewater are divided into physical methods, chemical methods, and biological methods. [5] Common treatment methods include adsorption, coagulation, electrochemical methods, advanced oxidation methods, and membrane separation methods. [6] Among various methods for treating dye wastewater, adsorption is a commonly used method due to its high efficiency, low energy consumption, and economy. It can remove harmful inorganic / organic substances from industrial wastewater. However, most adsorbents have poor performance and low selectivity, leaving considerable room for improvement in wastewater treatment. To develop green, inexpensive, and practical dye adsorbents, researchers have recently focused on natural and biodegradable polymers. [7] .

[0003] Sodium alginate is a natural polysaccharide extracted from brown algae (such as kelp or Sargassum) through seaweed crushing, strong alkali extraction, and calcium chloride precipitation of sodium carbonate. [8] The SA molecule is composed of β-D-mannuronic acid (M) and α-L-guluronic acid (G). [9] It is a linear anionic copolymer. β-D-mannuronic acid and α-L-guluronic acid residues are covalently linked together in different sequences or blocks to form...

[10] The compositional and structural differences between M-blocks and G-blocks significantly alter the gel properties of SA. Polymers with more M-blocks exhibit better elasticity but poorer water solubility, while polymers with more G-blocks are harder and more brittle but have better water solubility. The presence of numerous free carboxyl groups enables SA to undergo cross-linking reactions with various metal cations to form gels.

[11] , where Ca 2+ Ions are safe and non-toxic, widely available, and are the most commonly used ionic crosslinking agents.

[12] The metal ion-mediated gelation process of SA is mainly affected by factors such as SA concentration, M / G ratio, and metal ion concentration, while the requirements for pH and temperature conditions are not strict.

[13] This simplifies the preparation process of sodium alginate gel materials to some extent and enhances the controllability of the preparation process, laying the foundation for the widespread application of sodium alginate gel materials.

[0004] References

[0005] [1] Yin Ping. Research progress on advanced oxidation treatment technology for dye wastewater [J]. Guangdong Chemical Industry, 2021, 48(8): 186-187, 183.

[0006] [2] Shi Rui, Li Yili, Yin Jing, et al. Preparation of corn straw and activated carbon and its adsorption kinetics [J]. Journal of Environmental Engineering, 2014, 8(8); 3428-3432.

[0007] [3] Xu Nannan, Lin Dasong, Xu Yingming, et al. Effects of corn stalks and biochar on Cd 2+ Adsorption characteristics and influencing factors of [J]. Journal of Agricultural Environmental Science, 2014, 33(5): 958-964.

[0008] [4] Cui Yumin, Yin Rongcan. Research progress on treatment methods for dye wastewater [J]. Science & Technology Review, 2021, 39(18):79-87.

[0009] [5] China Resources Comprehensive Utilization, 2020, 38(11):94-96.

[0010] [6] AZBARN, YONART, KESTOGLUK. Comparison of COD and decolorization methods of various advanced oxidation processes and chemical treatment methods in polyester and acetate dyeing wastewater [J]. Chemical Circle, 2004, 55(1): 35-43.

[0011] [7] B.Galzerano,CICabello,M.Munoz,GGBuonocore,P.Aprea,B.Liguori,L.Verdolotti,Fabrication of green diatomite / chitosan-based hybrid foams with dye sorptioncapacity,Materials 13(2020)3760,https: / / doi.org / 10.3390 / ma13173760.

[0012] [8]FISET JF,BLAIS JF,RIVEROS P A.Review on the Removal ofMetal Ions from Effluents Using Seaweeds,Alginate Derivatives and Other Sorbents[J]. Revue des sciences de l eau,2008,21(3).

[0013] [9]Ruvinov E,Cohen S.AdvancedDrug Delivery Reviews,2016,96,54.

[0014]

[10] Teng K, An Q, Chen Y, et al. ACS Biomaterials Science & Engineering, 2021, 7(4), 1302.

[0015]

[11] Lee KY,MooneyD J.Progress in Polymer Science,2012,37(1),106.

[0016]

[12] Ching SH, Bansal N, Bhandari B. Critical Reviews in Food Science and Nutrition, 2017, 57(6), 1133.

[0017]

[13] Guo X, Wang Y, Qin YM, et al. International Journal of Biological Macromolecules, 2020, 162, 618. Summary of the Invention

[0018] The purpose of this invention is to provide a chitosan-sodium alginate-diatomaceous earth composite adsorbent, its preparation method, and its application. By employing a dropwise addition method, a sodium alginate solution infused with calcined diatomaceous earth is slowly added dropwise to a mixture of chitosan and CaCl2, successfully preparing the chitosan-sodium alginate-diatomaceous earth composite adsorbent. This innovative method effectively solves the problem of insufficient mechanical strength of sodium alginate hydrogels alone and significantly enhances the reusability and stability of the hydrogel microbead adsorbent.

[0019] To achieve the above objectives, the present invention provides the following technical solution:

[0020] A method for preparing a chitosan-sodium alginate-diatomaceous earth composite adsorbent includes the following steps:

[0021] (1) Calcining diatomaceous earth to obtain calcined diatomaceous earth;

[0022] (2) Dissolve sodium alginate powder in water to prepare sodium alginate solution;

[0023] (3) Weigh the calcined diatomaceous earth and add it to the sodium alginate solution to prepare mixture a;

[0024] (4) Weigh CaCl2 and add it to acetic acid solution and stir to dissolve it to obtain CaCl2 solution;

[0025] (5) Weigh out the chitosan powder and add it to the CaCl2 solution and stir until homogeneous to obtain mixture b;

[0026] (6) Mixture a is dropped into mixture b for cross-linking to prepare SA / DM / CS composite gel spheres;

[0027] (7) Rinse the SA / DM / CS composite gel ball several times with water, then freeze and thaw it several times before drying to obtain the chitosan-sodium alginate-diatomite composite adsorbent.

[0028] Preferably, the mass of sodium alginate powder in step (1) is 1-5g.

[0029] Preferably, the M / G ratio of the sodium alginate powder is 1-2:1.

[0030] Preferably, the mass of the calcined diatomaceous earth in step (3) is 1-5g.

[0031] Preferably, in step (6), the cross-linking time of mixing solution a into mixing solution b is 1 hour.

[0032] This invention also provides an application of a chitosan-sodium alginate-diatomaceous earth composite adsorbent in the adsorption of methylene blue.

[0033] Preferably, the pH of the adsorbent when adsorbing the methylene blue solution is 3-11.

[0034] Preferably, the concentration of the methylene blue solution is 100-500 mg / L.

[0035] Preferably, the adsorbent adsorbs the methylene blue solution for 180-240 minutes.

[0036] Compared with existing technologies, this invention exhibits significant technical advantages, specifically in the following aspects:

[0037] (1) In terms of preparation process, this invention ingeniously employs an innovative composite method. By carefully dripping a sodium alginate solution containing calcined diatomaceous earth into a carefully proportioned mixed solution of chitosan and CaCl2, sodium alginate-chitosan composite hydrogel microspheres are prepared, resulting in a composite adsorbent with a methylene blue removal rate of over 95%. This unique process not only cleverly combines the advantages of chitosan, sodium alginate, and diatomaceous earth, but also significantly improves the problem of insufficient mechanical strength in traditional single sodium alginate hydrogels. By introducing calcined diatomaceous earth, not only is the adsorption performance of the hydrogel microspheres enhanced, but its overall structural stability is also improved. Simultaneously, it provides diffusion channels for dye molecules within the microspheres, enabling the prepared chitosan-sodium alginate-diatomaceous earth composite adsorbent to exhibit higher durability and reliability in various complex environments. This innovation not only lays a solid foundation for the recyclability of hydrogel microsphere adsorbents but also greatly expands their scope and possibilities in practical applications, marking a significant technological breakthrough in the field of adsorption materials.

[0038] (2) In terms of performance, the chitosan-sodium alginate-diatomaceous earth composite adsorbent of the present invention exhibits excellent adsorption effect and outstanding stability. After five rigorous cycle tests, the removal rate of methylene blue by the adsorbent decreased only 5.08% from the initial 95.54% to 90.46%. This data fully demonstrates that the adsorbent of the present invention can maintain good adsorption capacity after multiple uses, and the performance decline is negligible. This high stability and continuously efficient adsorption performance not only means that the frequency of adsorbent replacement can be reduced and operating costs can be lowered in practical applications, but also means that the adsorbent has great potential and practical application value in treating industrial wastewater such as dye wastewater.

[0039] In summary, the chitosan-sodium alginate-diatomaceous earth composite adsorbent of the present invention not only solves the problem of low mechanical strength of traditional adsorbent materials through innovative preparation process, but also demonstrates its great potential in practical industrial applications through good adsorption effect and stability. Attached Figure Description

[0040] Figure 1 The graph shows the effect of sodium alginate dosage on the methylene blue removal rate.

[0041] Figure 2 The graph shows the effect of the sodium alginate G / M ratio on the methylene blue removal rate.

[0042] Figure 3 The graph shows the effect of diatomaceous earth addition on the methylene blue removal rate.

[0043] Figure 4 The graph shows the effect of solution pH on the removal rate of methylene blue.

[0044] Figure 5 The graph shows the effect of initial concentration on the adsorption capacity of methylene blue.

[0045] Figure 6 This is a diagram of a pseudo-first-order dynamic model;

[0046] Figure 7 This is a diagram of a pseudo-second-order dynamic model;

[0047] Figure 8 This is the adsorption isotherm at 298 K;

[0048] Figure 9 Here is the adsorption isotherm at 303 K;

[0049] Figure 10 This is the adsorption isotherm at 308 K;

[0050] Figure 11 This is a diagram of the cyclic adsorption experiment of the adsorbent. Detailed Implementation

[0051] The present invention will be further described in detail below with reference to specific embodiments. It should be emphasized that the following description is merely exemplary and is not intended to limit the scope and application of the present invention.

[0052] 1. Preparation method of chitosan-sodium alginate-diatomaceous earth composite adsorbent

[0053] 10g of diatomaceous earth (DM) was calcined at 450℃ for 4 hours at a heating rate of 10℃ / min. At room temperature, 1-5g of sodium alginate powder (M / G ratios of 1:2, 1:1, and 2:1) was dissolved in 200mL of deionized water to prepare a sodium alginate solution. 1-5g of the calcined diatomaceous earth was weighed and added to the sodium alginate solution for later use. 2g of CaCl2 was weighed and dissolved in 100mL of 2% acetic acid solution to prepare a CaCl2 solution. Then, 0.6g of chitosan powder was weighed and added to the CaCl2 solution and stirred until homogeneous. The sodium alginate solution was added dropwise to this solution to prepare SA / DM / CS composite gel sphere adsorbent, and crosslinked for 1 hour. The SA / DM / CS composite gel spheres were rinsed several times with ultrapure water. After repeated freeze-thaw cycles three times, the composite gel spheres were dried in a vacuum dryer for 24 hours (temperature -55℃, vacuum <10Pa).

[0054] The technical principle of the preparation method of this invention:

[0055] This invention presents an innovative method for preparing a chitosan-sodium alginate-diatomaceous earth composite adsorbent. This method not only integrates the advantages of various natural polymers and inorganic materials, but also achieves a significant improvement in adsorption performance through precise control of raw material dosages and process parameters in each step, demonstrating remarkable technological progress. The following is an in-depth analysis of each step of this preparation process and an explanation of the necessity for optimization:

[0056] (1) Pretreatment of diatomaceous earth (DM)

[0057] First, 10g of diatomaceous earth was selected as the basic support material. Its unique porous structure endows the adsorbent with excellent specific surface area and adsorption capacity. Calcination at 450℃ for 4 hours, with the heating rate precisely controlled at 10℃ / min, effectively removed impurities from the diatomaceous earth and enhanced its structural stability, providing a more solid foundation for subsequent composite processes. This optimized step ensures the efficient role of diatomaceous earth in the composite system and is a key step in improving the overall adsorption performance.

[0058] (2) Preparation of sodium alginate solution

[0059] Sodium alginate powder (1-5g) is dissolved in 200mL of deionized water to prepare a sodium alginate solution. Sodium alginate (M / G ratio of 1:2, 1:1, 2:1) not only acts as a binder but also significantly improves the hydrophilicity and biocompatibility of the adsorbent due to its abundant hydroxyl and carboxyl functional groups. By adjusting the amount of sodium alginate and the M / G ratio, the physical structure and chemical properties of the adsorbent can be finely controlled, thereby affecting its adsorption efficiency and selectivity for target pollutants. Optimizing this step is crucial for balancing adsorption performance and material cost, making it possible to achieve efficient and low-cost adsorption.

[0060] (3) Preparation and compounding of chitosan solution

[0061] 2g of CaCl2 was dissolved in 100mL of 2% acetic acid solution to form a CaCl2 solution. Then, 0.6g of chitosan powder was added and stirred thoroughly. Chitosan, as a natural polymer, has amino and hydroxyl groups that can form ionic crosslinks with sodium alginate, enhancing the mechanical strength and stability of the adsorbent. The introduction of chitosan also endows the adsorbent with more active sites, improving its adsorption capacity for specific pollutants. By precisely controlling the amount of chitosan added, the surface charge distribution and pore structure of the adsorbent can be further optimized, thereby achieving more efficient capture of target pollutants.

[0062] (4) Preparation and post-treatment of composite gel spheres

[0063] Sodium alginate solution was added dropwise to a mixture containing chitosan and CaCl2 to form SA / DM / CS composite gel spheres as adsorbents through a cross-linking reaction. The cross-linking time was set to 1 hour to ensure a complete reaction. Subsequently, the gel spheres were rinsed multiple times with ultrapure water to remove unreacted chemicals and impurities, ensuring the purity of the adsorbent. In particular, three repeated freeze-thaw cycles further enhanced the internal pores and adsorption sites of the gel spheres. Finally, the gel spheres were dried at -55°C using a vacuum freeze dryer (vacuum degree <10 Pa) for 24 hours. This step not only removed moisture from the adsorbent but also preserved its porous structure, ensuring the long-term stability of the adsorbent during storage and use.

[0064] (5) Significant progress in technical effectiveness

[0065] Through the precisely controlled preparation process described above, the resulting chitosan-sodium alginate-diatomaceous earth composite adsorbent exhibits excellent technical performance. It not only possesses high adsorption capacity but also demonstrates good regeneration and reusability, significantly reducing treatment costs. Furthermore, the green and environmentally friendly nature of this preparation method, along with the precise control of raw material dosage and optimization of process parameters, makes this adsorbent a promising candidate for application in the field of dye wastewater treatment.

[0066] 2. Adsorption Experiment

[0067] 0.1 g of adsorbent was placed in 100 mL of MB solution of a certain concentration. After adsorption for a certain period of time by shaking at 220 rpm in a water bath constant temperature shaker, the concentration of methylene blue remaining in the solution after adsorption was measured, and the adsorption capacity q of the adsorbent for the methylene blue solution was calculated. t The formulas for (mg·g⁻¹) and removal rate R (%) are as follows:

[0068]

[0069] Where, q t R represents the adsorption capacity of the adsorbent for MB, in mg / g; R represents the removal rate of MB by the adsorbent, in %; C0 represents the initial concentration of the MB solution, in mg / L; C e is the concentration of MB solution at adsorption equilibrium, mg / L; V is the volume of MB solution, L; m is the mass of adsorbent, g.

[0070] 3. Factors affecting adsorption performance

[0071] 3.1 Effect of sodium alginate dosage

[0072] Figure 1The figure shows the removal rate of MB by adsorbents with different amounts of sodium alginate. At an addition of 1g, the sodium alginate was too low to cross-link in the mixed solution; at 5g, the sodium alginate solution was too viscous to prepare hydrogel microspheres by dropwise addition. The figure shows that the hydrogel with an addition of 3g had the highest removal rate. This is because as the sodium alginate content increases, the number of adsorption sites in the hydrogel increases, thus improving its adsorption performance. However, excessive sodium alginate caused the hydrogel microspheres to increase in volume due to the excessive viscosity of the solution, resulting in a decrease in the specific surface area of ​​the hydrogel and affecting its adsorption performance. Therefore, 3g was chosen as the optimal addition amount of sodium alginate for subsequent experiments.

[0073] The effect of the 3.2G / M ratio

[0074] In sodium alginate, the mass fractions of components G and M can be expressed by their ratio (G / M), which is an important parameter characterizing sodium alginate. The curves showing the removal rate of methylene blue by adsorbents containing sodium alginate with different G / M ratios over time are shown below. Figure 2 As shown in the figure, the removal rate of methylene blue by the hydrogel gradually increases with the increase of the G / M ratio. This is because the hydrophilicity of SA is significantly enhanced with the increase of the G component (α-L-guluronic acid) content, thereby enhancing the adsorption performance of the hydrogel. Therefore, sodium alginate with a G / M ratio of 2:1 was used for subsequent studies.

[0075] 3.3 Effect of diatomaceous earth addition on methylene blue removal rate

[0076] Figure 3 The effect of different diatomaceous earth addition amounts on the removal rate of methylene blue was shown. Compared with the adsorbent without diatomaceous earth, the removal rate increased from 86.48% to 90.90%. The addition of diatomaceous earth increased the surface roughness of the adsorbent, providing more adsorption sites. With increasing diatomaceous earth addition, the removal rate increased from 90.90% to 95.46%. However, excessive diatomaceous earth reduced the removal rate because excess diatomaceous earth tends to aggregate within the adsorbent, negatively impacting adsorption. The figure shows that the adsorbent achieved optimal adsorption performance at an addition amount of 3g. Therefore, 3g will be used as the optimal addition amount of diatomaceous earth in subsequent experiments.

[0077] 3.4 Effect of solution pH

[0078] Solution pH directly affects the final removal rate through surface charge and the speciation of MB in the solution. For example... Figure 4As shown, as the pH value increased from 3 to 9, the removal rate of MB by the adsorbent gradually increased from 93.48% to 95.07%, while the removal rate decreased to 87.65% when the pH rose to 11. This indicates that the adsorbent exhibits good adsorption performance for methylene blue over a relatively wide pH range. This is because the adsorbent surface is electronegative at pH < 11, forming hydrogen bonds with the positively charged methylene blue. At higher pH conditions, the hydrolysis of methylene blue molecules is inhibited, and electrostatic repulsion exists, leading to a decrease in the adsorbent's adsorption capacity for methylene blue. Considering that the fresh methylene blue solution is weakly acidic, the pH used in the experiment was 5.

[0079] 3.5 Effect of initial concentration

[0080] like Figure 5 As shown, the equilibrium adsorption capacity gradually increases with increasing initial concentration, and the adsorption capacity of methylene blue varies with contact time. Due to the large concentration gradient as a driving force and the high-frequency continuous collisions between the adsorbent and adsorbate molecules, the adsorption driving force of methylene blue is affected by the initial concentration. The hydrogel adsorbent exhibits extremely rapid adsorption in the first 90 minutes. As adsorption progresses, the adsorption sites on the adsorbent surface are occupied by methylene blue molecules, and adsorption gradually slows down until it reaches adsorption equilibrium at approximately 180 minutes. Among these, 500 mg / L MB showed the fastest adsorption rate.

[0081] 4. Adsorption kinetics

[0082] The adsorption capacity of the adsorbent for methylene blue at different times was determined at 298 K, and the effect of different initial concentrations of methylene blue on the adsorption kinetics was analyzed. 0.1 g of adsorbent was added to MB solutions with different initial concentrations, and the concentration of residual MB in the solution was determined by UV-Vis.

[0083] To describe the mechanism of methylene blue adsorption by adsorbent microbeads, the adsorption kinetics of MB removal were studied using 100 ml of methylene blue solutions with different initial concentrations (100 mg / L, 200 mg / L, 300 mg / L, 400 mg / L, 500 mg / L) under experimental conditions of 25 °C and pH = 5. Experimental data for different initial concentrations were analyzed. The pseudo-first-order (3) and pseudo-second-order (4) models are generally expressed as follows:

[0084]

[0085]

[0086] In the formula q e and q t(the unit is mg / g) represent the equilibrium adsorption capacity and the adsorption capacity at time t (min), respectively. K1 and k2 represent the rate constants of the pseudo-first-order model and pseudo-second-order model, respectively. In the weber-morris model, k d represents the rate constant of the intraparticle diffusion model. The intercept C represents the boundary layer thickness, and a larger C indicates a greater boundary layer effect.

[0087] Plotting ln(q e -q t ) against t and plotting t / q against t can yield the calculated values of k1 and k2, and the related plots are shown in Figure 6 and 7 , and the parameters related to the kinetic models are shown in Table 1. The correlation coefficient of the pseudo-second-order equation is closer to 1. In addition, compared with the experimental values, the pseudo-second-order model obtains more accurate adsorption capacity values. Therefore, the pseudo-second-order model is more suitable for the adsorption of methylene blue by the adsorbent. The adsorption rate of methylene blue on the adsorbent is controlled by chemical adsorption through electron sharing or exchange between the adsorbent and the adsorbate.

[0088] Table 1 Kinetic model parameters for adsorption of methylene blue by the adsorbent

[0089]

[0090] 5. Adsorption isotherms

[0091] The experiments were carried out at 295, 303 and 308 K, respectively. 0.1 g of adsorbent was added to 100 mL of MB solution with a concentration of 500 mg / L. After adjusting the initial pH to 5, the adsorption experiment was carried out in a constant temperature oscillator at a rotation speed of 220 rpm. The residual MB concentration in the solution was determined by UV-Vis. The adsorption isotherm describes the equilibrium concentration of the adsorbate in the solution and the interaction behavior between the adsorbate and adsorbate molecules. The Langmuir model (5) assumes that the adsorbate forms a monolayer at specific homogeneous sites, while the Freundlich model (6) holds that adsorption occurs as multi-layer coverage of the adsorbate on a heterogeneous surface. These two adsorption isotherm models were used to fit the adsorption isotherms of MB on the adsorbent at temperatures ranging from 298 K to 308 K. In the Langmuir model, a separation factor R L (7) can be defined to determine the favorability and reversibility of the adsorption process. When 0 < RL < 1, it is a favorable adsorption process, and a larger R L indicates more favorable adsorption of pollutants by the adsorbent.

[0092]

[0093] In the formula, C e (mg / L) is the equilibrium concentration of the dye, and q e(mg / g) is the equilibrium adsorption capacity, qm (mg / g) is the maximum adsorption capacity, and K L and K F (L / mg) correspond to the Langmuir constant and the Freundlich constant, respectively. Langmuir constant K L (L / mg) is related to the affinity and free energy of adsorption, the slope of the Freundlich isotherm represents the adsorption strength, and 1 / n represents the heterogeneity factor that is beneficial to the adsorption process.

[0094] The adsorption isotherm fitted based on the adsorption data is shown below. Figure 8-10 The parameters are shown in Table 2. It can be seen that the equilibrium adsorption capacity of the adsorbent increases with increasing adsorption temperature, indicating that adsorption is an endothermic process. The correlation coefficient (RL) of the Langmuir model... 2 The correlation coefficients of the Langmuir model and the Langmuir model are significantly higher than those of the Freundlich model. The Langmuir model provides the best fit to the experimental data. Therefore, the adsorption of MB by the adsorbent is a monolayer adsorption on a homogeneous surface at heterogeneous adsorption sites. Furthermore, the 1 / n values ​​obtained from the Freundlich model are between 0 and 1, indicating that the adsorption of MB by the adsorbent is a preferred process.

[0095] Table 2. Langmuir and Freundlich model parameters for methylene blue on the adsorbent.

[0096]

[0097] 6. Repeatability Experiment

[0098] The regeneration and reuse rate of adsorbents are important factors to consider in practical industrial applications. 0.1 g of adsorbent was immersed in 100 mL of methylene blue solution (100 mg / L) with an initial pH of 5.0 and adsorbed at 298 K until adsorption equilibrium was reached. Then, desorption was performed in 0.1 M HCl solution. Under acidic conditions, H... + The interaction between the adsorption site and the adsorption site is stronger than the electrostatic interaction between methylene blue and the adsorbent, leading to the desorption of methylene blue from the adsorbent. The adsorption effect is as follows: Figure 11 After five cycles, the removal rate of methylene blue by the adsorbent decreased from the initial 95.54% to 90.46%, a decrease of only 5.08%, still demonstrating good adsorption effect and stability. This proves that the modified adsorption microspheres in this experiment also have great potential for practical industrial applications in the treatment of dye wastewater.

[0099] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. An application of a chitosan-sodium alginate-diatomaceous earth composite adsorbent in adsorbing methylene blue from wastewater, characterized in that, The pH of the adsorbent adsorbing the methylene blue solution is 5, the concentration of the methylene blue solution is 500 mg / L, and the adsorbent adsorbs the methylene blue solution for 180 min. The preparation method of the chitosan-sodium alginate-diatomaceous earth composite adsorbent includes the following steps: (1) Calcining diatomaceous earth to obtain calcined diatomaceous earth; (2) Dissolve sodium alginate powder in water to prepare sodium alginate solution; (3) Weigh the calcined diatomaceous earth and add it to the sodium alginate solution to prepare mixture a; (4) Weigh CaCl2 and add it to acetic acid solution and stir to dissolve it to obtain CaCl2 solution; (5) Weigh out chitosan powder and add it to CaCl2 solution and stir evenly to obtain mixture b; (6) Add mixture a to mixture b for cross-linking to form SA / DM / CS composite gel spheres; (7) Rinse the SA / DM / CS composite gel balls several times with water, then freeze and thaw them several times before drying to obtain the chitosan-sodium alginate-diatomite composite adsorbent. The mass of sodium alginate powder mentioned in step (2) is 3g; The M / G ratio of the sodium alginate powder is 2:1; The mass of the calcined diatomaceous earth mentioned in step (3) is 3g; In step (6), the cross-linking time for mixing solution a to be added to mixing solution b is 1 hour.

Citation Information

Patent Citations

  • Three-component cationic dye adsorbent and preparation method thereof

    CN103447008A